(untitled) (AYUSHDHARA, 2025)
Congenital insensitivity to pain with anhidrosis (CIPA) represents a rare genetic disorder characterized by complete absence of pain sensation and inability to sweat, primarily attributed to mutations in the NTRK1 gene. While modern medicine has elucidated the molecular mechanisms underlying this condition, traditional Ayurvedic medicine offers alternative perspectives through its constitutional framework and understanding of sensory dysfunction. Objective: This study explores the correlation between Ayurvedic principles and CIPA manifestations, examining how classical texts describe similar conditions and proposing an integrative approach to understanding this complex disorder. Methods: A systematic review of classical Ayurvedic texts including Charaka Samhita, Sushruta Samhita, and Ashtanga Hridaya was conducted alongside contemporary literature on CIPA. Comparative analysis focused on symptomatology, constitutional predisposition, and therapeutic approaches documented in traditional sources. Results: Ayurvedic literature describes conditions resembling CIPA under various terminologies including "Sparsha Ajna" (loss of tactile sensation) and "Sweda Abhava" (absence of sweating). The disorder correlates with specific Vata-Pitta constitutional imbalances, particularly affecting the nervous system and thermal regulation mechanisms described in classical texts. Conclusion: Integration of Ayurvedic understanding with modern genetic knowledge provides a holistic framework for comprehending CIPA, potentially offering complementary therapeutic strategies focused on constitutional management and symptomatic palliation.